KEBIJAKAN RI MELAKUKAN KERJASAMA SUMBER DAYA KELAUTAN PERIKANANDENGAN THAILAND - Putri, Nadya Eka; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In this time ZEEI resource exploiting go out to sea was high enough but result was obtained Indonesia nation and also state still is small. Where foreign ship activity which steal fish have entered 12 mile Indonesia often found in territorial water of West Aceh, North Sulawesi, territorial ocean of Arafuru, and some area which gristle to the happening of trespasser at least 1 million in a year ton result of Indonesia sea fisher have been taken by a number of foreign ship, from that case Indonesian have cooperation with Thailand fishery area specially in the case of resource development ocean of Indonesia and its bearing with problem of theft ilegal fishing. And the effort from fishery cooperation between Indonesia and Thailand in overcoming theft illegal fish and also its bearing with sea resources development, hence writer use framework idea of International Relations concept, International Maritime Law concept, Regional concept of Territorial Water, and also conception Reality Development of Oceanic and Fishery.To facilitate analysis and also get clarity pursuant to existing problems, hence writer use major premis for example : concept of Internasional Relation, Internatsional Law, concept of Internasional Cooperation, concept of International Agreement, while minor premis consist of : Region Territorial Water of Indonesia, Reality Development Oceanic of Indonesia. Thereby hence interesting writer of hypotesis that is ;‖ if Thailand and Indonesia doing fishery cooperation more foccused which have agreement in minilisize activity a theft of regional ilegal fish in territorial ocean of Indonesia by applying effective observation and staigtening of law expressly, hence resource ocean of Indonesia good involve and also non involving will expand to be marked the increasingof fishery productivity and the increasingof infrastructure development ocean in Indonesia‖.Finally writer conclude that Indonesia government still good enough to increase its ocean development with effort of observation and straightening of law expressly by doing cooperatin with Thailand in minilisize activity theft of illegal fish in ocean territorial of Indonesia.Keyword : Fisheries cooperation, illegal fishing, and development ocean in Indonesia.